The Influence of Traditional Approach, Movement Education in Learning of Physical Education, towards PhysicalFitness,Problem Solving Capabilities In Elementary School01,02,03 KemiriBanyumas Indonesia. - sejati, Restian Gigih; sejati, Restian gigih (Media Ilmu Keolahragaan Indonesia, 2016)
Purposes: (1) To know the difference of influences towards physical fitness between students who were taught using movement education approach with ones who were taught using traditional approach as well as the impacts on high class student groups, low class student groups. (2) To know the interaction ofphysical education learning approach towards physical fitness of student groups. (3) To know which one is the most effective advancement traditional approach or movement education. This research is experimental. The population: students of SD N 01,02,03Kemiri. 160 samples were collected (purposive sampling).Â  Free variables: traditional approach, movement education approach. Bound variables: physical fitness, and problem solving capabilities.Data collection: randomized group pre-test-post-test designs. Data analysis used (ANAVA). Conclusions: (1) There were different impacts between physical fitnessof Â students being taught using movement education approach with students being taught using traditional education with significance value 0.000 is 0.05 of F=1.491 as well as differences of impacts on the high class group and low class group with significance value 0.0000 is = 0.05 F=1.7773 (3) There were interactions of physical education learning approach towards the physical fitness of a group of students. (4) There were differences of impacts on the problem solving capabilities between students being taught using movement education approach and students being taught using traditional approach. (5) There were interactions of physical education learning approach towards problem solving capabilities. Movement education approach student group was more advanced than traditional approach probability 0.002 from the Table of between subjects effects Fhitung.Keywords:physical fitness, problem solving capabilities